Higher efficacy of direct hemoperfusion using coated activated-charcoal column for disopyramide poisoning: A case report. Issue 49 (December 2017) - Iguchi, Shigekazu; Yamaguchi, Naotaka; Takami, Hiroki; Komatsu, Takayuki; Ookubo, Hirokazu; Sekii, Hajime; Inoue, Kenji; Okazaki, Shinya; Okai, Iwao; Maruyama, Sonomi; Nomura, Tomohisa; Sugita, Manabu
Abstract: Rationale: Cases of severe disopyramide poisoning are rare and few have been reported. We report a case in which activated-charcoal column hemoperfusion was dramatically effective for life-threatening disopyramide poisoning. Patient concerns: A teenage girl who had overdosed on disopyramide (total dose, 4950 mg) was brought to our hospital. She was resuscitated from short period cardiopulmonary arrest and subsequently showed severe cardiogenic shock and ventricular arrhythmia. Diagnoses: Disopyramide poisoning (self-evident). Interventions: As hemodynamics remained unstable after providing percutaneous cardiopulmonary support and intra-aortic balloon pumping, we attempted direct hemoperfusion using a coated activated-charcoal hemoperfusion column. Outcomes: Hemodynamics including electrocardiography and serum disopyramide concentration were dramatically improved, and the patient was ambulatory by hospital day 14. Lessons: Because disopyramide has low molecular weight and a small distribution volume, blood purification is considered to be the most effective therapy. We selected direct hemoperfusion for relatively high protein-binding rate. In fact, clinical status was dramatically improved, and the calculated half-life of the direct hemoperfusion phase was the shortest of all phases. In cases of severe or life-threatening disopyramide poisoning, blood purification therapy including direct hemoperfusion using a coated activated-charcoal column should be performed.